Understanding Budget Reality in The Perspective of Symbolic Interactionism - Ardini, Lilis; Dewi, Nurul Hasanah Uswati (International Research Journal of Business Studies, 2016)
This study aims to interpret the meaning of budget on one of the StateOwned Enterprises (SOEs) to minimize conflict between principal and agent. Analysis is done using symbolic interactionism method in interpretive paradigm. Data collection is conducted using in-depth interviews with informants who are very familiar with budgeting in PT Perkebunan Nusantara (PTPN). The results of this study reveal that budgeting process involves the interaction and action between the principal and the agent based on their own experiences in preparing the budget. Decision making is sorely needed, especially in a condition where an individual is able to free himself from the crisis called epiphany. Epiphany is a moment of experience that makes an impression on one’s life so as to form a character is called epiphany. It could be said that epiphany is the most critical moment ever experienced by someone that cannot be forgotten(Denzim, 1989) Social fact describes that a capitalistic company ownership thinks of itself with the purpose of fulfilling personal desires and prosperity, so in implementing budget preparation consisting of the symbol of numbers, it is always covered by passion of greed. Conflict of interest is very noticeable when the preparation and adoption of the budget is filled with a variety of interests. Regulatory system is becoming part of legitimate stage of budgeting that has become the elements of capitalist company ownership that eventually reap capitalist values in the accounting information, in which the decisions and the economic actions are also based on the capitalist values. The implication of this research is expected to provide practical recommendations to the good cooperation between the agent and principal in preparing the budget.